PENGUATAN KAPASITAS APARATUR DESA MELALUI PENDAMPINGAN ADMINISTRASI PEMERINTAHAN DI KECAMATAN PARLILITAN KABUPATEN HUMBANG HASUNDUTAN - Iis Selpiani Barasa; Jusmer Sihotang (DEVELOPMENT: Journal of Community Engagement, 2025)
Village government administration constitutes an essential element in supporting governance implementation and public service delivery, as stipulated in Law Number 6 of 2014 concerning Villages. The implementation of village administration requires adequate capacity of village officials. Capacity refers to the ability, skills, understanding, attitudes, values, relationships, behaviors, motivation, resources, and conditions that enable individuals, organizations, networks, sectors, and broader systems to perform their functions in order to achieve established development goals over time. However, in practice, disparities remain in the level of capacity among village officials in understanding and implementing administrative governance in an orderly, systematic manner and in accordance with prevailing laws and regulations. In this context, Parlilitan Subdistrict, as part of Humbang Hasundutan Regency, holds a strategic role in providing guidance and assistance to village governments, as mandated by Law Number 23 of 2014 concerning Regional Government. This community service activity aims to enhance the capacity of village officials through administrative governance assistance conducted during an internship program at the Parlilitan Subdistrict Office. The implementation method employed a mentoring and participatory approach, involving students directly in governmental administrative activities and office services within the subdistrict environment. The results of the program indicate that administrative assistance effectively improved the understanding and skills of village officials in managing governmental administration, while also strengthening coordination between village and subdistrict governments. Ultimately, the administrative mentoring initiative contributes to improving the performance of village governance in Parlilitan Subdistrict, Humbang Hasundutan Regency.